Antidiabetic Activity of a Herbal Marketed Product Madhumeha Churna in Alloxan - Induced Diabetic Rats - Silawat, Narendra (International Journal of Pharmaceutical & Biological Archive, 2010)
<!--[if gte mso 9]> Normal 0 false false false EN-US X-NONE X-NONE MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--> <!-- /* Font Definitions */ @font-face {font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0;} /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal {mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin:0in; margin-bottom:.0001pt; mso-pagination:widow-orphan; font-size:12.0pt; font-family:"Times New Roman","serif"; mso-fareast-font-family:"Times New Roman";} .MsoChpDefault {mso-style-type:export-only; mso-default-props:yes; font-size:10.0pt; mso-ansi-font-size:10.0pt; mso-bidi-font-size:10.0pt;} @page Section1 {size:8.5in 11.0in; margin:1.0in 1.0in 1.0in 1.0in; mso-header-margin:.5in; mso-footer-margin:.5in; mso-paper-source:0;} div.Section1 {page:Section1;} --> <!--[if gte mso 10]> <![endif]-->The present study was performed to evaluate Madhumeha Churna for its antidiabetic activity in alloxan (100 mg/kg, i.p.) induced diabetic rats. The effects of Churna on fasting blood glucose level (BGL), oxidative stress parameters such as malondialdehyde (MDA) levels, and glutathione (GSH) in liver homogenates, were observed. Churna (200 mg/kg/day and 400 mg/kg/day p.o.) was administered to a group of diabetic rats (n=6) for 10 consecutive days and the observed data was compared with glibenclamide (n=6, 10 mg/ kg/ day p.o.). Administration of Churna causes a significant reduction of BGL (p< 0.01), MDA (p<0.001), GSH levels (p<0.05) vs diabetic control. Based on our data it can be concluded that Madhumeha Churna possess moderate antihyperglycemic effect and may effect GSH and MDA levels and has mixed effect on body & various organ weight